EKSPLORASI PENGALAMAN SISWA SEKOLAH DASAR DALAM MEMBANGUN MOTIVASI BELAJAR IPAS MELALUI MEDIA AUGMENTED REALITY - Putri Sahidah; I Made Ratih Rosanawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to explore elementary school students’ experiences in building learning motivation in Integrated Science and Social Studies (IPAS) through the use of Augmented Reality (AR) media at SDN Kenokorejo 04. The research was motivated by students’ difficulties in understanding abstract concepts, low engagement, and limited learning media that relied mainly on textbooks. A qualitative approach with a phenomenological design was employed to deeply examine students’ subjective experiences. The participants consisted of fourth-grade students and a classroom teacher selected through purposive sampling. Data were collected through participatory observation, in-depth interviews, and documentation, and analyzed using the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing, supported by NVivo software. The findings indicate that the use of AR media created an interactive and meaningful learning experience that contributed to the development of students’ learning motivation. Students expressed feelings of enjoyment, enthusiasm, and curiosity, as learning felt similar to playing a game. AR visualization helped them understand abstract concepts more concretely, increased their confidence in asking questions and participating in discussions, and encouraged active involvement in problem-solving activities. The study concludes that Augmented Reality serves not only as a visual learning aid but also as an meaningful pedagogical medium to foster confidence, active engagement, and intrinsic motivation among elementary school students in IPAS learning.